ANTIULCER ACTIVITY OF ETHANOL LEAF EXTRACT OF Azadirachta indica IN ALBINO RATS - TIMOTHY, S.Y; RALPH, I.E; MOH’D, A.S; NACHANA, A.T; TAS, MIDALA; SABASTINE, A.Z, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
Azadirachta indica is used as a traditional remedy in ayurvedic medicine in India since antiquity and many parts of Africa including Nigeria to treat gastric ulcer. Current study was designed to investigate this plant leaves for potential antiulcer agent in aspirin induced ulcers in rats. Qualitative pytochemical screening and acute oral toxicity test of the ethanol leaf extract of Azadirachta indica was carried out according to standard methods previously described. Gastric ulcer was induced by oral administration of aspirin (300 mg/kg) to adult rats. The antiulcer activity was determined by calculating the mean decrease in number of epithelial shedding, frank haemorrhage, ulcers and perforations in the extract-treated rats at doses of 150, 300 and 600 mg/kg. Preliminary phytochemical screening of the ethanolextract of Azadirachta indica leaf revealed the presence of carbohydrates, reducing sugar, saponins, anthraquinones, flavonoids, tannins and alkaloids. The oral median lethal dose (LD50) of the extract was estimated to be greater than 5000 mg/kg in rats. The extract was found to be an effective antiulcerogenic agent at different doses (150, 300 and 600 mg/kg). Oral administration of all the investigated doses of the extract reduced the severity of gastric mucosal damage. The extract showed a significant (p<0.05) protection against aspirin induced epithelium shedding at lower doses (150 mg/kg and 300 mg/kg) comparable to the standard drugs used misoprostol and omeprazole. Frank haemorrhage index was reduced by the extract at higher doses of 300 and 600 mg/kg with no statistically significant difference with omeprazole (p>0.05). The ethanol leaf extract of Azadirachta indica contains phytochemical constituents which may be responsible for its antiulcer activity and these amply justifies the traditional use of this plant in managing gastrointestinal disorders including peptic ulcer disease.